Extinction and permanence of two-nutrient and one-microorganism chemostat model with pulsed input - Xinyu Song; Zhong Zhao (Discrete Dynamics in Nature and Society)
A chemostat model with periodically pulsed input is considered. By using the Floquet theorem, we find that the microorganism eradication periodic solution (u1∗(t),v1∗(t),0) is globally asymptotically stable if the impulsive period T is more than a critical value. At the same time we can find that the nutrient and microorganism are permanent if the impulsive period T is less than the critical value.